2018
DOI: 10.1002/1873-3468.13305
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid baicalin improves glucose metabolism by targeting the PH domain of AKT and activating AKT/GSK3β phosphorylation

Abstract: Baicalin is one of the main flavonoids of the dried root of Scutellaria baicalensis Georgi and is reported to exert beneficial effects on the regulation of glucose/lipid metabolism. However, understanding its specific target and unique mechanism for improving glucose utilization is a challenge. In this paper, target fishing with a baicalin probe reveals that baicalin interacts with AKT. An immunofluorescence assay further demonstrates the colocalization of baicalin with AKT in the cytoplasm. A competitive test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…5% bovine serum albumin (containing 0.05% Triton X-100) was added to close the cells for 2 h. After TBST washing, primary antibody cyclin D1 (1:100) was added and incubated overnight at 4 °C. After TBST washing, IgG secondary antibody (FSA; SAlexa Fluor 594, 1:5000) was added and incubated in the dark at 37 °C for 1 h. Then, 100 μL of BDP reaction solution (20 μM BDP TMR azide, 40 μM triazolamide, 20 μM CuSO 4 , and 40 μM sodium ascorbate) was added and treated at room temperature for 1 h (click to react as shown in Scheme ). After an appropriate number of washes, fluorescence images were obtained by confocal microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…5% bovine serum albumin (containing 0.05% Triton X-100) was added to close the cells for 2 h. After TBST washing, primary antibody cyclin D1 (1:100) was added and incubated overnight at 4 °C. After TBST washing, IgG secondary antibody (FSA; SAlexa Fluor 594, 1:5000) was added and incubated in the dark at 37 °C for 1 h. Then, 100 μL of BDP reaction solution (20 μM BDP TMR azide, 40 μM triazolamide, 20 μM CuSO 4 , and 40 μM sodium ascorbate) was added and treated at room temperature for 1 h (click to react as shown in Scheme ). After an appropriate number of washes, fluorescence images were obtained by confocal microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Baicalin was reported to alleviate the neuronal apoptosis induced by ketamine toxicity (Zuo et al, 2016) and protect neonatal brains against hypoxic-ischemic injury via activation of PI3K/Akt signaling pathway (Zhou et al, 2017). A recent study showed that baicalin might directly bind to the pleckstrin homology domain of AKT and activate the phosphorylation of AKT on Ser473 site (Yang et al, 2019). Geniposide was reported to protect against hypoxicischemia-induced brain injury through the activation of PI3K/Akt signaling pathway (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…AKT acts as a central regulator of cellular metabolism downstream of insulin signaling that is responsible for the regulation of glucose metabolism. 63 , 64 In vivo experiments support that AKT2 plays a key role in the regulation of glucose metabolism. 65 , 66 Researchers have found that germline mutations of AKT occur during the tumorigenesis and progression of some cancer.…”
Section: The Pi3k/akt Signaling Pathway In Tumorigenesismentioning
confidence: 99%